DAMPAK COVID-19 TERHADAP EVALUASI PEMBELAJARAN DI SEKOLAH - Andi Fatmmayanti; Tri Susantri (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This study aims to determine the impact of Covid-19 on the implementation of evaluations in schools using a descriptive survey research method with a sample of 15 teachers. Data collection techniques in this study using a questionnaire. The data analysis technique consists of the editing stage, the data input stage and the tabulation stage, which then calculates the frequency of the data and then presents it as a percentage. The results showed the percentage level of each aspect, namely: 1) Difficulty in carrying out evaluations 21.19%, 2) Application of evaluation methods that were fun for students 41.6%, 3) Student score gain during online learning 22.52% and student achievement 15,23%. The conclusion of this study is that Covid-19 has a negative impact on the implementation of learning evaluations in schools due to the unpreparedness of learning facilities and infrastructure in schools to carry out online learning so that it is necessary to increase the creativity and quality of teachers' pedagogic competencies through workshops and seminars, as well as equitable distribution of technological developments. All regions in Indonesia have adequate internet access.